An Attempt to Choke John Bull with Irish-Made Dishes. - Jones, Thomas Howell (active 1824-1848) ? (Fores, S. W., 1829)
Scholarly notes may be added at a later date.
1 print : col.
Keywords: Caricatures; Cartoons; Nelson's Pillar ?; Catholic emancipation; Great Britain -- Relations -- Ireland; John Bull (Symbolic character)